An Interdisciplinary Approach for Management of Missing Canines with Implant Supported Cantilevered Prosthesis - Karanjit, Anugya; Pradhan, Shaili; Shrestha Gorkhali, Ranjita; Koirala, Pramod Kumar; Adhikari, Suchana (Journal of Nepalese Society of Periodontology and Oral Implantology, 2022)
Missing tooth in the anterior region of the maxilla lies in aesthetic zone and create quite noticeable discrepancies. With a paradigm shift in the patient expectations towards functional as well as aesthetically appealing replacements for edentulism, the implant based oral rehabilitation has emerged as a sole winner in fulfilling all aspects of patient needs. Interdisciplinary team treatment planning is a paramount approach for achieving optimal final aesthetics. This article aims to present a case report of replacement of bilaterally missing maxillary canine and lateral incisors with cantilever prosthesis using an interdisciplinary approach.